Climate Variability Indices—A Guided Tour - Mateusz Norel; Michał Kałczyński; Iwona Pińskwar; Krzysztof Krawiec; Zbigniew W. Kundzewicz (Geosciences, 2021)
The objective of this study is to provide a comprehensive review and characterization of selected climate variability indices. While we discuss many major climate variability mechanisms, we focus on four principal modes of climate variability related to the dynamics of Earth’s oceans and their interactions with the atmosphere: the El Niño–Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), Pacific Decadal Oscillation (PDO), and Atlantic Multi-decadal Oscillation (AMO). All these oscillation modes are of broad interest and considerable relevance, also in climate impact studies related to teleconnections, i.e., relationships between climate variations at distant locations. We try to decipher temporal patterns present in time series of different oscillation modes in the ocean–atmosphere system using exploratory analysis of the raw data, their structure, and properties, as well as illustrating the quasi-periodic behavior via wavelet analysis. With this contribution, we hope to help researchers in identifying and selecting data sources and climate variability indices that match their needs.